Peran Hubungan Masyarakat (Humas) dalam Pengelolaan Layanan Informasi E-Government di Kantor Kementerian Agama Kabupaten Gresik - Dalilah Ayu Permatasari; Irsyadatun Ni’mah Almatin; Wiladatus Sholihah (Jurnal Administrasi Pendidikan Islam, 2021)
Public relations in an organization aims to create a positive image of the organization in public. Government public relations provide services, disseminate information and provide education to the public regarding policies and institutional work programs for the public. Management of information services can be accessed through social media, one of which is the website. E-government is an activity carried out by the government using information technology support in providing services to the community. The purpose of this study was to determine the role of public relations in managing e-government information at the Office of the Ministry of Religion, Gresik Regency. This study used a qualitative descriptive research method with a phenomenological approach, while the informants of this study were the Gresik Ministry of Religion's public relations officers. Data collection techniques were carried out by observation, interviews and documentation. Based on the results of data reduction, the results of this study indicate that the role of public relations in the management of e-government information services at the Office of the Ministry of Religion of Gresik Regency has not been implemented optimally.